Narrativas sobre a crise econômica mundial e crise das representações: o que a crise evidencia? - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This dissertation is themed narrative horizon of reflection and analysis on the global economic crisis triggered initially in the US in 2008, as well as its theoretical and empirical articulation with the central idea of ​​the research, namely, that the crisis in question is closely related the implications of globalization in the context of a theoretical and epistemological break whose main expression is the generalized crisis of collective representations. He tried to at first expose and question the notion of globalization in order to encourage an understanding of globalization to serve as a theoretical assumption and pay for labor purposes. The second time I present the various narratives about the crisis, said on the one hand, in theoretical works (Harvey, Boaventura, Touraine, Bauman), and another in analysis of records extracted from a digital file built from the systematization data (articles, interviews, files etc.) of three email addresses (CartaMaior, IhuOnline and OutrasPalavras). Finally, we seek to articulate the moments mentioned above, in order to operate the sense connections between the global economic crisis, globalization, crisis of collective representations and thus point out the sociological implications arising therefrom, in other words, at the last moment I say that the crisis shows, on the one hand, contradictions and more acute turbulence of a period of historical and epistemological rupture on the other, the redefinition of the classic collective representations by intensifying struggles, conflicts and resistance (indignados, Occupy, Trek June etc.) against a totalitarian globalization that privileges the financial market and in favor of other globalizations and ways of producing and living who value life and its people. Conflicts and resistance in the long and medium term determined the become of the nation state and its sovereignty; Democracy and its legitimacy, given the hegemonic globalization and alter-globalizations against hegemonic. We are inside an historic delivery!
Keywords: Ciências sociais; Crise econômica; Globalização; Ambiente da rede; Globalization; Environment Network; CIÊNCIAS HUMANAS: SOCIOLOGIA